City Branding Design from the Identification of Local Values of Penajam Paser Utara Regency - Tajri M, Fulkha; Ngabito, Olivia Febrianty; Huldiansyah, Denny; Sherlia; Yendra, Sasferi (VCD: Journal of Visual Communication Design, 2023)
Penajam Paser Utara Regency is in a strategic location to improve its brand identity. Its existence adjacent to the new State Capital (IKN) is an opportunity with great potential for developing all Penajam Paser Utara Regency (PPU) sectors. The natural wealth in the form of the sea, endemic fauna in the form of sambar deer, Mastogok traditional motifs and some rice-producing areas that can be said to be the granary of IKN food security are local values that will be visualized in the form of a logo that characterizes Penajam Paser Utara Regency, plus a location that can be said to be "Serambi Nusantara" which means that PPU is the front porch / front page of IKN. The method in designing the city branding logo of Penajam Paser Utara Regency is practice-based (Practice-based research) because the foundation at the beginning is the experience of directly observing and obtaining data directly from the community, regional officials, and local customary leaders. The stages in this method include observation, improvisation, and realization. Ultimately, this paper shows a comprehensive design process for creating a visual identity for a city/district, which begins with research, visual enrichment, and visual design finalization.